Strengthening Financial Planning Competence Among Senior High School Students Through a Participatory School-Based Educational Intervention - Irna Maya Sari; Muchamad Rizky Fauzi; Siti Agistriyani; Dhea Putri Anggraeni (Jurnal Pengabdian Masyarakat, 2026)
Purpose: This community service program aims to strengthen financial planning competence among students of SMAN 2 Krakatau Steel, Cilegon, in response to persistently low financial literacy levels among senior high school students. The program specifically targets students from an industrial-zone school serving diverse socioeconomic backgrounds, where a baseline needs assessment revealed limited budgeting habits and high susceptibility to impulsive spending driven by digital wallet adoption. Method: The program was conducted on April 23, 2026, involving 50 students from grades 10 and 11 majoring in Social Sciences (IPS), through five sequential stages: basic financial literacy education, practical financial planning training, digital media implementation, responsible financial behaviour campaign, and mentoring and monitoring. Evaluation was conducted using pre-test and post-test instruments. Participants were selected based on curriculum relevance and school readiness. The 30% improvement threshold was established based on prior Indonesian community service benchmarks (Muthia et al., 2023; Arifin et al., 2025). Ethical considerations including participant awareness and institutional coordination were observed throughout. Practical Applications: The program produced an average 38.4% improvement in financial literacy scores, a financial education module, a digital financial recording template, and the formation of student financial literacy agents capable of continuing peer education. It is important to note that these gains reflect short-term knowledge and skill improvements; sustained behavioral change requires longitudinal follow-up, which is scheduled six months post-intervention. Conclusion: This program significantly and measurably improved students' financial knowledge, skills, and attitudes. The integrative approach, combining theory, hands-on practice, and digital media, proved effective. Findings should be interpreted with caution given the single-day format and absence of a control group. The program contributes a replicable school-based model for financial literacy interventions in industrial-area contexts.